An Example Case of System Error in Evaluation of Medical Malpractice - Yıldırım, Mahmut Şerif; Odabaşı, Aysun Balseven; Köse, Çetin; Lale, Aykut; Tümer, Ali Rıza (The Bulletin of Legal Medicine, 2018)
Medical malpractice, which is defined as “patients’ harm resulting from healthcare professionals’ improper and unethical attitude or insufficient and sloppy practice”, is strictly limited to healthcare professionals’ errors in practice. However, it should include system error analysis. In this article, a missed case of system error resulted in death is presented to remind the concept to Forensic Medicine experts and review the literature. A 20-year-old male who underwent renal transplantation from a live donor, underwent graft nephrectomy due to acute accelerated rejection. The patient with cardiac overload findings in the postoperative period, collapsed while the patient was being sent to a special center for urgent dialysis due to lack of functional dialysis unit. In the transfer ambulance, there was no oxygen source and the patient was unable to actively ventilate. The patient died while under intensive care. In our evaluation, system error has been detected and the administration was held responsible. The experts who are asked about the medical malpractice have to take the basic concept of "medical error" as a basis for considering the mistakes of medical applications not only from the point of view of health professionals.